Ocorrência da infecção por Cryptosporidium spp. em cabritos (Capra hircus) - de Brito, Roberta Lomonte Lemos [UNESP]; Inácio, Sandra Valéria [UNESP]; dos Santos Oliveira, Dalilian Antoniete; de Sousa, Maximiana Mesquita; Meireles, Marcelo Vasconcelos [UNESP]; Lobo, Raimundo Nonato Braga; da Silva Vieira, Luiz; Bresciani, Katia Denise Saraiva [UNESP] (My University, 2014)
The present study aimed to determine the occurrence of infection by Cryptosporidium spp. in goat kids from Quixadá, Ceará, Brazil. The study included 400 goat kids of both sexes, 3 to 360 days old, with or without defined breed, originating from 25 farms distributed in three circuits. Feces were registered in accordance with the appearance and color, distributed into tubes Eppendorf tubes and frozen in natura at-20°C until the moment of extraction of genomic DNA from the parasite with the aid of a commercial kit. For amplification of fragments of the 18S subunit of ribosomal RNA (rRNA) was used to Nested PCR. The occurrence of Cryptosporidium spp. in goats kids of the Quixadá was 7.50% (30/400). The frequency in the dry period and rainy was 9.55% (19/199) and 5.47% (11/201) respectively (χ2=2.39 and P>0.05). Positive samples were identified in 64.00% (16/25) of the studied farms, and from these samples 50.00% (15/30) and 70.00% (21/30) had feces with normal appearance and color respectively, suggesting that the asymptomatic goats were eliminating oocysts. No positivity for Cryptosporidium spp. was observed in 301 to 360-day-old goats, demonstrating that older animals have less chance to become infected with the parasite.
Occurrence of infection by Cryptosporidium spp. in goat kids (Capra hircus)
Keywords: Age; Asymptomatic; Cryptosporidium spp.; Diarrhea; Dry period; Goats; Nested-PCR